2011
DOI: 10.1073/pnas.1018487108
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of SLX4 in interstrand cross-link repair is regulated by the Fanconi anemia pathway

Abstract: Interstrand cross-links (ICLs) block replication and transcription and thus are highly cytotoxic. In higher eukaryotes, ICLs processing involves the Fanconi anemia (FA) pathway and homologous recombination. Stalled replication forks activate the eight-subunit FA core complex, which ubiquitylates FANCD2-FANCI. Once it is posttranslationally modified, this heterodimer recruits downstream members of the ICL repairosome, including the FAN1 nuclease. However, ICL processing has been shown to also involve MUS81-EME1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
160
3
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 178 publications
(170 citation statements)
references
References 50 publications
(69 reference statements)
6
160
3
1
Order By: Relevance
“…[156][157][158][159][160] Similar to FAN1 and FANCD2, FANCP/SLX4 and FANCD2 co-localize in nuclear foci and co-immunoprecipitate. 154 While Yamamoto and colleagues established that the FANCP/SLX4 UBZ domain and the monoubiquitination of FANCD2 are required for FANCP/SLX4 targeting to nuclear foci, a recent report has contradicted these findings and shown that SLX4 recruitment occurs independent of FANCD2 monoubiquitination. 154,161 Taken together, these findings suggest that one major function for chromatin-bound monoubiquitinated FANCD2 may be the recruitment of structure-specific endonucleases that mediate key incision steps during the process of ICL repair.…”
Section: Fancd2: Recruitment Of Nucleasesmentioning
confidence: 78%
See 1 more Smart Citation
“…[156][157][158][159][160] Similar to FAN1 and FANCD2, FANCP/SLX4 and FANCD2 co-localize in nuclear foci and co-immunoprecipitate. 154 While Yamamoto and colleagues established that the FANCP/SLX4 UBZ domain and the monoubiquitination of FANCD2 are required for FANCP/SLX4 targeting to nuclear foci, a recent report has contradicted these findings and shown that SLX4 recruitment occurs independent of FANCD2 monoubiquitination. 154,161 Taken together, these findings suggest that one major function for chromatin-bound monoubiquitinated FANCD2 may be the recruitment of structure-specific endonucleases that mediate key incision steps during the process of ICL repair.…”
Section: Fancd2: Recruitment Of Nucleasesmentioning
confidence: 78%
“…145 While FAN1 mutations have yet to be uncovered in FA patients, mutations in FAN1 have been identified as a cause of karyomegalic interstitial nephritis, a chronic kidney disease. 151 Mutations in the SLX4 gene were recently uncovered in FA complementation group P. [152][153][154] FANCP/SLX4 is a »200 kDa multidomain protein that, similar to FAN1, harbors an aminoterminal UBZ domain.…”
Section: Fancd2: Recruitment Of Nucleasesmentioning
confidence: 99%
“…Disruption of Slx4 in chicken cells has revealed it to be cellularly essential-at odds with yeast, mouse and human systems [18,56,57,128,129]. This may be a peculiarity of chicken, due to its abnormal complement of nucleases-as it lacks both Mus81 and Ercc1 but has orthologues of Xpf and Eme1.…”
Section: A Specific Molecular Defect In Fanconi Anaemiamentioning
confidence: 99%
“…This may be a peculiarity of chicken, due to its abnormal complement of nucleases-as it lacks both Mus81 and Ercc1 but has orthologues of Xpf and Eme1. In this system Xpf is cellularly essential, which is also in contrast to human, mouse and yeast [114,128,130]. This makes the analysis of nucleases involved in crosslinking very difficult in chicken cells.…”
Section: A Specific Molecular Defect In Fanconi Anaemiamentioning
confidence: 99%
“…Moreover, this variant targets the UBZ4 domain (Ubiquiting-Binding Zinc finger motif 4) essential for SLX4 interaction with multiple-partner proteins, 14 and recruitment to sites of DNA damage. 16 Indeed, four FA patients harbor SLX4 splicing mutations causing in-frame exon 5 skipping, 8,9 supporting that the UBZ4 domain (encoded by exon 5) is clinically relevant. Other variants do not appear to represent disease-causing mutations, in particular those detected in control samples, but some might represent low-or moderate-risk alleles contributing to the overall cancer risk.…”
Section: Discussionmentioning
confidence: 99%